Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cryst11101163
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Synergistic Extraction of Lithium from Spent Lithium Cobalt Oxide Batteries by Molten Salt Electrolysis and Two-Step Precipitation Method

Abstract: With the continuous development of society, the number of spent lithium-ion batteries has also increased, and the recovery of valuable metals such as Ni, Co, and Li has become the main research direction of many scholars. In this paper, the extraction process of lithium that enters the molten salt after LiCoO2 electrolysis is studied. Oxalic acid and phosphate are added to molten salt containing lithium ions to realize the two-part precipitation method to extract lithium. The influence of pH value, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The regenerated LiCoO 2 exhibited 93 % of capacity retention after 100 cycles. An experiment that added phosphate and oxalic acid to the molten salt for obtaining lithium phosphate precipitate was conducted by Li [149] . Influences of temperature, pH value, reaction time, even oxalic acid or phosphate addition were analyzed and the precipitation of Li 3 PO 4 reached 88.44 %.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…The regenerated LiCoO 2 exhibited 93 % of capacity retention after 100 cycles. An experiment that added phosphate and oxalic acid to the molten salt for obtaining lithium phosphate precipitate was conducted by Li [149] . Influences of temperature, pH value, reaction time, even oxalic acid or phosphate addition were analyzed and the precipitation of Li 3 PO 4 reached 88.44 %.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Although this method requires more steps in processing to convert Li phosphate into Li carbonate or hydroxide, it might cut down on processing time and costs [72]. Sodium phosphate salts, including di-sodium phosphate, tri-sodium phosphate, sodium pyrophosphate, and sodium tri-polyphosphate, have been utilized in various research studies [73][74][75][76]. The study conducted by Alsabbagh et al [76] showed suitable salts for lithium-precipitating reagents, with tri-sodium phosphate (TSP) recovering 40% of lithium in the Dead Sea evaporated end brine.…”
Section: Precipitationmentioning
confidence: 99%
“…[33][34][35] This synergistic extraction process has garnered significant research attention for metal ion separation or purification, 36,37 and is generally explained in terms of the formation of an extraction complex that includes participation of more than one molecular species. 38,39 Chang et al in 2017 used oleic acid as the liquid organic phase to study the extraction of copper ions from water (Fig. 1(a)).…”
Section: Introductionmentioning
confidence: 99%
“…33–35 This synergistic extraction process has garnered significant research attention for metal ion separation or purification, 36,37 and is generally explained in terms of the formation of an extraction complex that includes participation of more than one molecular species. 38,39…”
Section: Introductionmentioning
confidence: 99%